A Diachronic View into an Understanding of Technology Acceptance: Where to Go through TAM for Teacher Education from Global to Local? - ; Nurdan Kavakl? Uluta? (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Technology acceptance is rooted at the center of the growing body of research in lieu of education, educational technology, and teacher education. This is mainly occupied with the idea of integrating technology into the classroom setting in order to trigger learners to be advanced in higher-order thinking skills and be digitally literate in order to cope with the challenges of the information era. In doing so, teachers, as the gatekeepers of technology in the classroom, are renowned to be vital sources to deliver information. Thus, it is of critical importance to detect whether teachers are accepting technology with ease and as useful, which can be explained through the technology acceptance model (TAM). That said, this study adopts a diachronic view into an understanding of the role of TAM in teacher education. Accordingly, the aim of this article is to provide an overview of the lay of the land for the development of TAM together with the theories and variables beneath it by means of a review of existing literature. Conceptualizing where to go by means of a top-down approach from global (worldwide) to local (the Turkish context), this article scrutinizes the following results: (1) since new-age learners are expected to develop 21st-century skills, it is today’s necessity for future teachers to develop their knowledge and skills in technology; (2) this, in turn, holds the requirement for new teacher education programs to renew the already existing curriculum by providing multimodal learning and teaching environments; (3) herein, understanding how teachers perceive ease of use and usefulness of technology in order to employ it in the classroom environment is of critical importance to trigger teachers’ technology adoption through TAM as a credible model; however, TAM somehow falls short of unveiling what it means to adopt and integrate technology in classroom settings, though.